2020
DOI: 10.1073/pnas.1910952117
|View full text |Cite
|
Sign up to set email alerts
|

Cancer epithelia-derived mitochondrial DNA is a targetable initiator of a paracrine signaling loop that confers taxane resistance

Abstract: Stromal-epithelial interactions dictate cancer progression and therapeutic response. Prostate cancer (PCa) cells were identified to secrete greater concentration of mitochondrial DNA (mtDNA) compared to noncancer epithelia. Based on the recognized coevolution of cancer-associated fibroblasts (CAF) with tumor progression, we tested the role of cancer-derived mtDNA in a mechanism of paracrine signaling. We found that prostatic CAF expressed DEC205, which was not expressed by normal tissue-associated fibroblasts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Upon this stimulation, fibroblasts secrete C3a in reactive oxygen species (ROS) dependent manner. Then C3a in a paracrine fashion promotes disease progression and docetaxel resistance by increasing tumor cell proliferation and survival ( 103 ). In a subcutaneous xenograft of human PC3 prostate cell line, the authors demonstrated superior efficacy of docetaxel and C3aR inhibition over docetaxel alone in decreasing tumor burden.…”
Section: Sites Of Complement Production and Activationmentioning
confidence: 99%
“…Upon this stimulation, fibroblasts secrete C3a in reactive oxygen species (ROS) dependent manner. Then C3a in a paracrine fashion promotes disease progression and docetaxel resistance by increasing tumor cell proliferation and survival ( 103 ). In a subcutaneous xenograft of human PC3 prostate cell line, the authors demonstrated superior efficacy of docetaxel and C3aR inhibition over docetaxel alone in decreasing tumor burden.…”
Section: Sites Of Complement Production and Activationmentioning
confidence: 99%
“…Interestingly, C3a-induced activation of the C3a receptor in prostate cancer cells drives docetaxel resistance in mouse models. mtDNA was also found in the plasma of docetaxel-treated patients supporting the hypothesis that therapy resistance in prostate cancer patients may occur by this crosstalk [63]. In mouse models, combination therapy of docetaxel with a C3aR inhibitor showed increased efficacy in limiting tumor growth when compared to docetaxel alone.…”
Section: Prognostic and Therapeutic Implications Of Microenvironmentamentioning
confidence: 53%
“…Neil Bhowmick expanded on the stromal considerations for prostate cancer therapy by presenting findings that demonstrated chemotherapy-triggered crosstalk between CAFs and tumor cells. His team found that docetaxel induces mitophagy and ER stress in prostate tumor cells, leading to secretion of mitochondrial DNA (mtDNA) [63]. This results in TLR9 activation in CAFs and release of C3a, a complement protein.…”
Section: Prognostic and Therapeutic Implications Of Microenvironmentamentioning
confidence: 99%
“…Mt-DNA has been shown to induce TLR9-mediated NF-κB activation driving regulatory polarization in macrophages in liver cancer ( 59 ) as well as activation of neutrophils in various forms of injury ( 60 ). Further, non-immune cancer-associated fibroblasts were also shown respond to mt-DNA via TLR-9 contributing to therapeutic resistance to taxanes ( 40 ). In addition to inflammatory modulation, mutations in tumor mt-DNA can also regulate mitochondrial metabolism in recipient cells ( 61 ) but have not been well-studied in the context of myeloid immunity.…”
Section: Tumor Evs and Myeloid-driven Inflammationmentioning
confidence: 99%